Effectiveness and safety of therapeutics used for treatment of experimental or spontaneous Mycoplasma infections - V. A. Agoltsov; L. P. Padilo; O. P. Biryukova; M. M. Ligidova (Ветеринария сегодня, 2022)
Mycoplasmoses of cattle and small ruminants,  pigs and poultry are widely spread and the infection process is frequently associated with other diseases. Mycoplasma spp. cause inflammatory respiratory diseases, diseases of joints and meninges, keratoconjunctivitis, mastitis and endometritis,  abortion and stillbirths. Etiotropic therapy of mycoplasmal infections consists in prescribing antibiotics: enrofloxacin, difloxacin, oxytetracycline, chlortetracycline, doxycycline, tylosin, tilmicosin, tylvalosin, tiamulin, florfenicol, lincomycin, spectinomycin, tulathromycin. The results of studies described in different publications show high sensitivity of Mycoplasma synoviae and Mycoplasma gallisepticum to tetracyclines, tiamulin and tylvalosin. Isolates with increased resistance to tilmicosin are also resistant to tylosin and lincomycin. Treatment of respiratory infections in lambs, the main causative agents  of which are Mannheimia haemolytica and Mycoplasma, has been successful with the use of fluoroquinolones, tilmicosin, tulathromycin, chlortetracycline, enrofloxacin, doxycycline, and oxytetracycline. Isolates of Mycoplasma bovis are largely sensitive to oxytetracycline, florfenicol and tulathromycin.  Enrofloxacin has a less pronounced therapeutic effect. Tilmicosin and oxytetracycline are effective in the treatment of respiratory diseases of young cattle, associated with Mycoplasma spp. Tulathromycin and tilmicosin have a significant therapeutic effect in the treatment of pneumonia in weaned piglets experimentally infected with Mycoplasma hyopneumoniae. Multiple (course) use of enrofloxacin significantly increases the therapeutic effect. Tilmicosin is effective in the control of other bacterial infections of pigs (pasteurellosis, streptococcosis, hemophilic polyserositis, infectious atrophic rhinitis).The general prophylaxis of mycoplasmal infections is to comply with veterinary and sanitary standards and to implement quarantine measures in the infection outbreak.